Hovercraft structural design testing using finite element method - Dianna Ratnawati; Setuju, Setuju; Khaharsyah, Alfat; Azwan, Hasnul (Universitas Sarjanawiyata Tamansiswa, 2024)
Indonesia is an archipelagic country and is a developing country and not all of its territory has easy roads to traverse, and some parts of its territory are still swamps. Hovercraft are one solution to reach areas that are difficult to pass by this type of vehicle. In this research, before carrying out the hovercraft fabrication process, design testing was carried out in this research. Design testing was carried out using the Finite Element Method (FEM). This test aims to determine whether the hovercraft design that will be fabricated will have sufficient strength in terms of construction. On the construction side, it is hoped that the hovercraft will have a long life cycle (fatigue testing) and good material strength. Design testing was carried out with a load of 250 kg (passenger); 500 kg (machine) and type I or H aluminum construction for better force and stress propagation. The results of this research include that the hovercraft construction design is suitable for use with a 250 kg passenger load and engine load. This is shown in the discussion which includes details from von Mises stress which is lower than the yield strength of aluminum, total deformation, to damage and life cycle fatigue.